Revitalisasi Materi Pendidikan Agama Islam Dalam Menumbuhkan Sikap Toleran Terhadap Keberagaman di Era Pluralisme - Saepul Saepul (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2025)
The modern era of pluralism demands Islamic religious education to face complex challenges in building tolerant attitudes toward diversity. This research aims to analyze the revitalization of Islamic Religious Education (IRE) materials to foster students' tolerant attitudes toward religious, cultural, and social plurality. The research method employs a qualitative approach with case studies in three senior high schools with multicultural students. Data were collected through classroom observations, in-depth interviews with IRE teachers and students, and curriculum document analysis. Data analysis techniques used the Miles and Huberman model with source triangulation. The research results show that revitalization of IRE materials through integration of Islamic pluralism values, interfaith dialogue, and contextual approaches can improve students' understanding of religious tolerance by 78%. The revitalized materials include the concepts of rahmatan lil alamiin, ukhuwah insaniyah, and local wisdom from an Islamic perspective. Implementation of learning based on dialogical discussions and diversity case studies proved effective in developing empathy and respect for differences. This research recommends developing an IRE curriculum that is adaptive to multicultural contexts by emphasizing religious moderation values, as well as teacher training in implementing inclusive learning approaches to strengthen social harmony in the era of pluralism.